HIV and Aging in the Era of ART and COVID-19. (1st February 2022) - Pallikkuth, Suresh; Pahwa, Savita
Abstract: Our understanding of HIV/AIDS has been reframed during the recent past because the use of novel antiretroviral therapy has enabled clinicians and patients to control the progression of the disease. This supplement provides an overview of the HIV and Aging in the Era of ART and COVID-19, a virtual symposium held on February 8–9, 2021, organized by the Miami Center for AIDS Research along with articles contributed by some of the speakers and members of the organizing committee and presentations by junior investigators.